2020
DOI: 10.3390/s20226427
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration Estimation with Small UAVs in Precision Agriculture

Abstract: Estimating evapotranspiration (ET) has been one of the most critical research areas in agriculture because of water scarcity, the growing population, and climate change. The accurate estimation and mapping of ET are necessary for crop water management. Traditionally, researchers use water balance, soil moisture, weighing lysimeters, or an energy balance approach, such as Bowen ratio or eddy covariance towers to estimate ET. However, these ET methods are point-specific or area-weighted measurements and cannot b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 130 publications
0
12
0
4
Order By: Relevance
“…With an available orthomosaic approach that is effective at reducing inconsistencies currently experienced with standard blending modes, improved farm management can be realized through reduction of wind effects and enabling quantification of errors using our proposed STD approach between neighboring orthophotos. While the literature provides examples of many precision agricultural applications for UAV-based thermal infrared data, including surface flux retrievals for evapotranspiration studies [51], phenotyping [28], plant water stress assessment [52], and irrigation scheduling [53], they suffer from inconsistencies that would inevitably be introduced by wind effects, especially wind direction, and the existing orthomosaic approaches. Even when applying best-practice field data collections of temperature-controlled ground references [54], inconsistencies from wind effects and the generation of an orthomosaic still exist within the dataset.…”
Section: Discussionmentioning
confidence: 99%
“…With an available orthomosaic approach that is effective at reducing inconsistencies currently experienced with standard blending modes, improved farm management can be realized through reduction of wind effects and enabling quantification of errors using our proposed STD approach between neighboring orthophotos. While the literature provides examples of many precision agricultural applications for UAV-based thermal infrared data, including surface flux retrievals for evapotranspiration studies [51], phenotyping [28], plant water stress assessment [52], and irrigation scheduling [53], they suffer from inconsistencies that would inevitably be introduced by wind effects, especially wind direction, and the existing orthomosaic approaches. Even when applying best-practice field data collections of temperature-controlled ground references [54], inconsistencies from wind effects and the generation of an orthomosaic still exist within the dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, remote sensing has been used for large scale ET estimation providing high spatial and temporal resolution. Several models and algorithms, such as Mapping evapotranspiration at high resolution with internalized calibration (METRIC), the Two-source energy balance (TSEB) model, and machine learning have been used and discussed [79]. Recently, DL learning has been introduced to improve the ET estimation based on remotely sensed data.…”
Section: Evapotranspiration Estimationmentioning
confidence: 99%
“…Nowadays, UAVs are economically affordable and their ability to be flown at different altitudes and speeds make them helpful for photogrammetry and remote sensing (RS) techniques [3]. Their use is particularly extended in precision agriculture due to their capability to house onboard visible, thermal, and near-infrared sensors for acquiring aerial images of cultivated fields quickly in non-destructive and cost-effective ways [4][5][6][7][8][9][10][11]. In fact, UAVs have been widely used in the last 30 years in precision agriculture [12].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, UAVs have been widely used in the last 30 years in precision agriculture [12]. A comprehensive review on UAV-based applications in precision agriculture can be found in [1,[4][5][6][7][8][9][10][11][12][13], and several UAV onboard sensors for remote sensing are reviewed in [14]. Deployment of any UAV application involves the integration of several issues.…”
Section: Introductionmentioning
confidence: 99%